A general methodology to establish the contact force model for complex contacting surfaces. (June 2020) - Ma, Jia; Chen, Guangsong; Ji, Lei; Qian, Linfang; Dong, Shuai
Highlights: We develop an inverse research strategy towards the establishment of contact force model between complex geometries. Investigation on the combination between finite element simulation and parameter identification process is conducted. The verified GA-SQP estimation method is employed to acquire the unknown dynamical parameters. A new contact force model between barrel and bourrelet is developed. Abstract: In recent years, numerous studies have been conducted regarding the modeling of contact/impact events between smooth contacting surfaces, i.e. spheres and cylinders. Contrastingly, less attention has focused on the contact process between bodies with complex surfaces. In this paper, we develop an inverse research strategy towards the establishment of contact force model for complex contacting surfaces, namely, extracting the relevant dynamical parameters, like contact stiffness coefficient K, damping factor χ and exponent n, by utilizing parameter identification methods. Taking the contact process between barrel and bourrelet of projectile as our research object, the finite element elastoplastic dynamic model is firstly built. After that, the changes of several physical quantities during the contact process under different initial indentation velocities can be acquired, including the contact force, indentation, and the corresponding indentation velocity, which provide input data for the following parameter identification process. The mapping relationship between input variables can be assumed. Then, the genetic algorithm-sequential quadratic programing (GA-SQP) hybrid estimation method is employed to obtain the unknown contact dynamical parameters under each initial indentation velocity. Relation between each unknown dynamical parameter and initial indentation velocity can be fitted using the least square method. Hence, the contact force model specialized for contact process between barrel and bourrelet can be established. Finally, the dynamic equations of projectile – barrel coupled system considering the effect of rigid – flexible coupling during the artillery launching process are established, and the proposed contact force model is employed to quantify the contact responses between barrel and bourrelet. Simulation results obtained show great agreements with those of recent dissertation and live ammunition firing.